Effects of Disasters on Mental Health - Deniz S. Yorulmaz; Havva Karadeniz (Doğal Afetler ve Çevre Dergisi)
As a natural or human-induced event that occur unexpectedly, disasters affect society and people profoundly, cause loss of life and property, and lead to economic losses. Disasters pose an important public health problem due to their sudden nature, disruption in health services and society, severe economic impact, disruption in psycho-social wellbeing, resulting severe health problems in later periods, and loss of life and property. Each year, thousands of people are exposed to disasters in the world and in Turkey, and are affected by disasters in different ways. Although different age groups react differently after disasters, post-traumatic stress disorder, anxiety and stress disorder, depression, sleep and eating disorders are the most common problems. Through appropriate interventions and psychological first aid made according to age groups, mental health problems that can be seen after disasters can be controlled and reduced significantly. Thus, this review study discusses the effect of disasters on psycho-social health and the interventions that need to be made according to age groups